Studi Semiotik Feminisme pada Film Marlina Si Pembunuh dalam Empat Babak (Analisis Semiotika Roland Barthes) - Sharifa Arifin; Muhammad Syukron Anshori (CV. Publikasi Indonesia, 2022)
Background : Film is one of the modern mass communication media as an information medium that has the ability to convey messages. One of the Indonesian films that carries the theme of feminism is the film Marlina The Murderer in Four Acts which is also directed by a woman, Mouly Surya. Objective : To find out more about the signs of feminism that exist in the two characters Marlina and Novi in ​​the film Marlina The Murderer in Four Acts directed by Mouly Surya. Methods : This study uses a qualitative approach to the theory of semiotic analysis of Roland Barthes. The primary data used is data obtained directly from the object of research, namely the film Marlina The Killer in Four Acts and secondary data obtained from scientific sources that can support this research. significant two stages and their mythical elements. Results : This film tells the story of a woman who struggles against the patriarchal system where she gets violence and sexual harassment and the resistance of women in this film is very different from the stereotype in general where women are described as gentle figures. Conclusion: The results of this study show signs of feminism with two female characters with different characters but able to fight, this film indicates feminism but has an element of masculinity. In this film, it is legal to use masculine attributes to seize the goals of feminism, which in this study femininity cannot be limited by symbols and attributes.